2019
DOI: 10.3892/mmr.2019.9981
|View full text |Cite
|
Sign up to set email alerts
|

Effects of tyrosol and farnesol on Candida albicans biofilm

Abstract: The present in vitro study examined the effects of the quorum-sensing molecules farnesol and tyrosol on the development of Candida albicans biofilm in order to elucidate their role as novel adjuvants in oral hygiene. The investigation was conducted in C. albicans ATCC 10231 and C. albicans isolates from dentures and was performed in flat-bottomed 96-well polystyrene plates. Yeast growth and their capacity to form biofilms were evaluated following 24 and 48 h incubations at 37°C in Sabouraud broth supplemented … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 33 publications
1
30
0
Order By: Relevance
“…In comparison to other non-auris Candida species where lower concentrations of farnesol were reported to have anti-biofilm effects, our results showed higher concentrations are required to inhibit biofilm formation and development. Sebaa and co-workers (2019) reported anti-biofilm activity of farnesol against C. albicans ATCC 10231 and 6 other strains isolated from dentures [42]. In the same study, it was reported that 3 mM farnesol exerted stronger action when added at the beginning of biofilm formation (>50% inhibition) than when added to 24h mature biofilms (<10% inhibition), and therefore concluded farnesol had a greater effect during the initial phases of biofilm formation.…”
Section: Farnesol Inhibits C Auris Biofilm Development and Formationmentioning
confidence: 95%
“…In comparison to other non-auris Candida species where lower concentrations of farnesol were reported to have anti-biofilm effects, our results showed higher concentrations are required to inhibit biofilm formation and development. Sebaa and co-workers (2019) reported anti-biofilm activity of farnesol against C. albicans ATCC 10231 and 6 other strains isolated from dentures [42]. In the same study, it was reported that 3 mM farnesol exerted stronger action when added at the beginning of biofilm formation (>50% inhibition) than when added to 24h mature biofilms (<10% inhibition), and therefore concluded farnesol had a greater effect during the initial phases of biofilm formation.…”
Section: Farnesol Inhibits C Auris Biofilm Development and Formationmentioning
confidence: 95%
“…However, this effect was independent of the fungistatic or fungicidal effect. The researchers stated that by the addition of exogenous quorumsensing molecules, the related mechanism may be disrupted or the adhesion of microorganisms on the surface may be limited (Sebaa et al 2019). On the other hand, farnesol, a hydrophobic drug, has been reported to have antimicrobial effects against certain pathogens such as S. mutans.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the effect of farnesol against C. tropicalis and other yeasts isolated from fruit juice filtration membranes in mono-and multispecies biofilms was assessed (Agustín et al 2019). Similarly, the combination of tyrosol with other antifungals (amphotericin B, itraconazole, and fluconazole) showed a synergistic effect against C. albicans and C. tropicalis biofilms (Sebaa et al 2019). By contrast, nitric oxide (NO), a recognized QSM, enhanced the biofilm formation of S. cerevisiae through FLO11-independent mechanisms (Yan and Bassler 2019).…”
Section: Natural Compounds Against Yeast Biofilmsmentioning
confidence: 99%